Community Empowerment through Layering Method Compost Making Training as an Effort to Sustainable Organic Waste Management - Mochamad Rifky Fauzan; Cut Farra Maghfira Try Ananda Putri; Shofi Siti Nursabila; Meisya Fajriah Safari; Rahmah Nurul Salam; Herlan Suhaemi; M Zafar Shidiq; Siti Nurasiah; Agus Sobar; Engkus Engkus (Siber Nusantara of Community Service Review, 2026)
Household organic waste is an environmental problem that is still often not managed optimally, so it has the potential to cause pollution. This Community Service Activity (PKM) aims to improve community knowledge and skills in managing organic waste through training on making compost layering method in Nanggeleng Village, Citamiang District, Sukabumi City. The method used is Participatory Action Research (PAR) with the stages of problem identification, socialization, practical training, and monitoring and evaluation. The training was carried out by utilizing household organic waste which was arranged in layers between green materials and brown materials to support the decomposition process. The results of the activity showed an increase in public understanding, skills, and awareness in organic waste management as well as the ability to practice composting independently. This program contributes to reducing the volume of household waste and supports the creation of a clean, healthy, and sustainable environment.